mAb806 binding to epidermal growth factor receptor: a computational study - Ng, Yao Zong (2016)
The epidermal growth factor receptor (EGFR) is an important target in the treatment of cancer. A very potent antibody, mAb806, has been developed against overexpressed EGFR and was found to be particularly active in brain tumors. Structural studies reveal that it binds to an epitope on the extracellular region of the EGFR. However, this epitope is cryptic/buried in crystal structures of the active (untethered) and inactive (tethered) EGFR, and it is unclear as to how the antibody interacts with this region. To explore this interaction, we combined molecular docking, steered molecular dynamics, and equilibrium molecular dynamics simulations. Our computational models reveal that the antibody induces local unfolding around the epitope to form the antibody–EGFR complex. In addition, regions in the vicinity of the epitope also modulate the interaction, which are in accordance with several other known antibody–antigen interactions, and offers new possibilities for the design of antibodies with increased potency and specificity for this receptor.